KETERLIBATAN KERJA TERHADAP KOMITMEN ORGANISASI PADA DOSEN DI UNIVERSITAS NEGERI JAKARTA - MAUNA MAUNA; MIFTHA SAFITRI (Journal of Research and Measurement in Psychology, 2015)
This study aims to examine empirically whether there is influence between job involvement to organizational commitment. The subject were 221 lecturer of State University of Jakarta (UNJ) selecting using incidental sampling technique. This type of research is a quantitative research, data collection techniques using research data obtained through survey instruments adapted from previous researchers. Instruments made have been tested for validity and reliability, and belonging to the reliable criteria. Research hypothesis testing was performed using linear regression analysis of the predictors, with the job involvement as a predictor variable. The analysis shows a correlation coefficient of 0,000, less than the significance level (0.05). This value is interpreted that there are significant job involvement to organizational commitment. The influence of job involvement against organizational commitment in this research is 24.2%. So this research indicates that the influence of job involvement against organizational commitment lecturers of the State University of Jakarta.